Modern Approach to The Treatment of Complicated Forms of Chronic Purulent Inflammation of The Middle Ear - Hatamov J.A; Amonov Sh.E; Muxammadiyev O.Sh; Boltayev A.I. (Genius Journals, 2024)
Chronic purulent otitis media with complications is a serious disease that requires an integrated approach to diagnosis and treatment. The problem of timely identification and adequate treatment of people with chronic inflammation of the middle ear with complications remains relevant in the field of otolaryngology. This pathology includes various local and intracranial complications that can seriously affect the prognosis and quality of life of patients. Mortality from complications inside the cranial cavity is estimated at 20 to 50% and is practically not related to the time of surgical treatment of the inflammatory focus. The purpose of our study was to select tactics for complex diagnosis and treatment of chronic purulent otitis media with complications. We observed 114 patients with chronic suppurative otitis media (CSOM) for the period 2013- 2023. Of these, 85 patients with local, 29 patients with intracranial complications. All patients underwent a general clinical examination, radiography of the mastoid process using the Schüller and Mayer methods, computed tomography of the mastoid process, magnetic resonance imaging of the brain, consultation with a neurosurgeon, neurologist, ophthalmologist and other specialists. To clarify the diagnosis and differential diagnosis, all patients with purulent meningitis underwent a spinal puncture. The patients' condition gradually improved, and clinical and biochemical parameters normalized. This was usually observed after surgical debridement of a purulent focus of the mastoid process, drainage of brain abscesses, removal of a blood clot from the sinus, and intensive drug therapy. Thanks to modern diagnostic methods and a system of comprehensive emergency surgical and intensive treatment, it was possible to improve treatment outcomes and reduce mortality in chronic purulent otitis media with complications
Keywords: Chronic purulent otitis media; epitympanitis; mesotympanitis